2016
DOI: 10.18632/oncotarget.6813
|View full text |Cite
|
Sign up to set email alerts
|

RASSF1A inhibits gastric cancer cell proliferation by miR-711- mediated downregulation of CDK4 expression

Abstract: Although interaction with DNA repair proteins has demonstrated that RASSF1A is a tumour suppressor gene, much attention has been directed in recent years towards its roles in regulating the cell cycle. However, the precise mechanism remains unclear. Uncovering how RASSF1A participates in regulating the cell cycle is critical to exploring effective therapeutic targets for gastric cancer. Here we show that RASSF1A could regulate 14 miRNAs’ expression in the typical human gastric cancer line SGC-7901, of which mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Uncontrolled cell division, a core factor for cancer initiation, is mainly mediated by the imbalance of cell cycle machinery such as activation of cyclins and/or cyclin-dependent kinases (CDKs) 21 . Dysregulated cyclin or CDK activity is involved in almost all types of human cancers 20 , 22 29 . And the regulatory mechanisms of cyclins or CDKs in cancer oncogenesis and progression are also under exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled cell division, a core factor for cancer initiation, is mainly mediated by the imbalance of cell cycle machinery such as activation of cyclins and/or cyclin-dependent kinases (CDKs) 21 . Dysregulated cyclin or CDK activity is involved in almost all types of human cancers 20 , 22 29 . And the regulatory mechanisms of cyclins or CDKs in cancer oncogenesis and progression are also under exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had reported that BCL-2 induced apoptosis of mitochondrial cells, indicating that BCL-2 played a role in tumor development by blocking apoptosis ( 19 ). BCL-2 expression was higher in multiple cancers and regulated by various miRNAs, such as pancreatic adenocarcinoma regulated by miR-126 ( 20 ), breast cancer regulated by miR-27a ( 21 ), gastric cancer by miR-711 ( 22 ), pancreatic cancer by miR-1180 ( 23 ). A previous study reported that BCL-2 expression was obviously increased in SN-SCC ( 24 , 25 ) and it is involved in the tumor cell proliferation, migration, invasion and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the inconsistent findings, the biological functions of miR-711 remain unclear. In our previous study, we showed that the expression of miR-711 in gastric cancer tissues and cells was low, and that exogenous miR-711 expression inhibited gastric cancer cell invasion and migration by an unidentified mechanism (17). In this study, exogenous miR-711 overexpression in SGC-7901 or MGC-803 gastric cancer cells inhibited cancer cell invasion and migration.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, we confirmed that the expression of miR-711 in gastric cancer tissues was also low. Further investigation demonstrated that miR-711 inhibited gastric cancer cell invasion and migration, however the mechanism was unclear (17). In the present study, we demonstrated that miR-711 regulated EMT of gastric cancer cells by downregulating CD44 expression both in vivo and in vitro.…”
Section: Inhibition Of Epithelial-mesenchymal Transition In Gastric Cmentioning
confidence: 51%
See 1 more Smart Citation